Polysomnography assessment of sleep and wakefulness in premature newborns - Llaguno, Nathalie Sales; Goncalves Pedreira, Mavilde da Luz; Machado Avelar, Ariane Ferreira; Avena, Marta Jose; Tsunem, Miriam Harumi [UNESP]; Pinheiro, Eliana Moreira (Assoc Brasileira Enfermagem, 2015)
Objective: to describe the total sleep time and its stages, total wake time, heart rate values and oxygen saturation shown by premature infants, and the infl uence of the periods of the day on sleep and physiological parameters. Method: a descriptive study was conducted of 13 hospitalized premature infants. Data collection was performed using polysomnography and unstructured observation for 24 uninterrupted hours. Results: the newborns remained asleep for 59.6% of the day, predominantly in quiet sleep, with a higher mean heart rate during wakefulness (p<0.001). No difference was found between the variables related to sleep, physiological parameters and periods of the day, but in the morning a predominance of quiet sleep was observed (p= 0.002). Conclusion: the preterm newborn presented more total sleep time than wakefulness; quiet sleep was the predominant stage, and heart rate was higher during wakefulness.
Keywords: Sleep; Newborn; Neonatal Nursing